An updated assessment of the trade and poverty nexus in Latin America - Paolo Giordano; Kun Li (Inter-American Development Bank (IDB), 2012)
Despite the growing political priority given to making trade work for the majority in Latin America, a notable gap exists in the knowledge about the distributive impacts of trade integration. This study attempts to fill this gap: it surveys the most recent contributions to the mainstream trade economics literature, assesses their relevance for Latin America and concentrates on specific quantitative empirical available on the region. It concludes that despite the impossibility to rigorously and unambiguously assert that trade openness is conducive to growth and poverty reduction, the preponderance of evidence supports this conclusion. However, the majority of empirical studies also show that the impact of trade on growth and poverty is generally small and that the causes of indigence are to be found elsewhere. Likewise, it is extremely arduous to find evidence that supports the notion that trade protection is good for the poor.
hdl:11319/4209
Keywords: F14; F15; F16; 330; Trade; Trade Policy; Poverty; Inequality; Latin America